Abuso de alcohol y deterioro cognitivo en adultos. - Luna Hermoza, Yajaira Veronica (2025)
Research on alcohol abuse and cognitive impairment in adults, with the variables alcohol abuse and cognitive impairment, is driven by the importance of analyzing alcohol intake and its harmful consequences on mental functions. This bibliographic study aims to describe alcohol abuse and cognitive impairment in adults. The methodology is based on a quantitative, descriptive, and cross-sectional cohort review. A non-probability sample of 21 studies was selected using the CRF-QS instrument. Results: Different consumption patterns are evident according to the NIAAA criteria, including moderate drinking, binge drinking, heavy drinking, excessive alcohol consumption, and alcohol use disorder. These categories allow us to understand how different forms of consumption impact mental health, especially when high-risk behaviors are present. Regarding cognitive impairment, functions such as working memory, emotional memory, prospective memory, attention, language, thinking, executive functions, verbal fluency, processing speed, cognitive flexibility, inhibitory control, orientation, calculation, and motor skills were identified as being compromised to varying degrees. Impairment is influenced by variables such as frequency, duration, and quantity of consumption, as well as age and individual factors. Conclusion: Alcohol abuse in adults has a clear and significant impact on cognitive functioning; identifying consumption patterns and recognizing the mental processes affected are essential for designing effective prevention, early intervention, and rehabilitation strategies.